2018
DOI: 10.1159/000495399
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Consensus Sequence-Binding Protein 8, a Tumor Suppressor, Suppresses Tumor Growth and Invasion of Non-Small Cell Lung Cancer by Interacting with the Wnt/β-Catenin Pathway

Abstract: Background/Aims: Interferon consensus sequence-binding protein 8 (IRF8) belongs to a family of interferon (IFN) regulatory factors that modulates various important physiological processes including carcinogenesis. As reported by others and our group, IRF8 expression is silenced by DNA methylation in both human solid tumors and hematological malignancies. However, the role of IRF8 in lung carcinoma remains elusive. In this study, we determined IRF8 epigenetic regulation, biological functions, and the signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Cells in the control group were maintained in serum-free DMEM medium. For the experimental groups, HMrSV5 cells were treated with high glucose (25 μM) and lipopolysaccharide (LPS0, 910 μg/ml) for 24 h. As for the role of 1,25(OH) 2 D3, HMrSV5 cells were pre-incubated with 1,25(OH) 2 D3 (10 −6 mol/L) for 2 h and subsequently treated with high glucose (25 μM) and LPS (10 μg/ml) for 24 h. Wnt agonist 1, 0.7 μM for 12 h (MedChem Express, Monmouth Junction, NJ, USA) was also used, as previously described [23]. Glucose, LPS, and 1,25(OH) 2 D3 were purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Cells in the control group were maintained in serum-free DMEM medium. For the experimental groups, HMrSV5 cells were treated with high glucose (25 μM) and lipopolysaccharide (LPS0, 910 μg/ml) for 24 h. As for the role of 1,25(OH) 2 D3, HMrSV5 cells were pre-incubated with 1,25(OH) 2 D3 (10 −6 mol/L) for 2 h and subsequently treated with high glucose (25 μM) and LPS (10 μg/ml) for 24 h. Wnt agonist 1, 0.7 μM for 12 h (MedChem Express, Monmouth Junction, NJ, USA) was also used, as previously described [23]. Glucose, LPS, and 1,25(OH) 2 D3 were purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Interferon is a cytokine synthesized and secreted by immune cells, glial cells, and neuronal cells, and has antiviral, antitumor and immunomodulatory effects. 9 At present, the clinical use of intramuscular or subcutaneous injection for herpes zoster has a certain therapeutic effect, but systemic medication often has adverse reactions such as fever, allergy, and cytopenia. Guo et al 10 reported low-dose recombinant human interferon-α2b is used for the treatment of herpes zoster in patients with herpes zoster.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we found that hypermethylated DMRs in 3 regions (TSS200, TSS1500, and gene body) are significantly higher than hypomethylated ones. Furthermore, 15 tumor suppressor genes belonging to the HyperDown group were identified, of which CDO1 (Cysteine Dioxygenase Type 1) [ 59 , 60 ], IRF8 (Interferon Regulatory Factor 8) [ 61 ], STAT5A (Signal Transducer And Activator Of Transcription 5A) [ 62 ], CFTR (CF Transmembrane Conductance Regulator) [ 63 ], ADAMTS8 (ADAM Metallopeptidase With Thrombospondin Type 1 Motif 8) [ 64 ], WIF1 (WNT Inhibitory Factor 1) [ 65 ], GATA5 (GATA Binding Protein 5) [ 66 ], FOXA2 (FOXA2) [ 67 ], SHISA3 (Shisa Family Member 3) [ 68 ], AXIN2 (Axin 2) [ 69 ], DIRAS3 (DIRAS family GTPase 3) [ 70 ], IRX1 (Iroquois Homeobox 1) [ 71 ], and ITGA5 (Integrin Subunit Alpha 5) [ 72 ] are confirmed by previous studies to be silenced via hypermethylation in lung cancer ( Tables S1–S3 ). Although the tumor suppressor CAMK2N1 (Calcium/Calmodulin Dependent Protein Kinase II Inhibitor 1) has not been associated with lung cancer yet, its hypermethylation has been shown to promote tumorigenesis in other cancers [ 73 ].…”
Section: Discussionmentioning
confidence: 99%